RASIO HUKUM DAN IMPLIKASI HUKUM PENGUJIAN PENYALAHGUNAAN WEWENANG MENURUT PASAL 21 UNDANG-UNDANG ADMINISTRASI PEMERINTAHAN - M. Ikbar Andi Endang (Puslitbang Hukum dan Peradilan bekerja sama dengan Ditjen Badimiltun, 2020)
In the context of government action as a center point relate to public law protection, state administration jurisdiction along with its function as “judicature” (justiele functie – judicial function) belongs to characteristic of and/or repressive function. However, norm of Article 21 in Act Number 30 in 2014 about State Administration provide authority to State Administration Court to conduct assessments, whether there is any abuse of authority in decision making and/or administrative action (discretion) requested by an institution and/or an official of government administration, brings legal implication in form of a change in legal politic direction related to law enforcement in corruption crime eradication in this country in forms of preventive efforts, which is similarly as important as the corruption crime eradication itself, because corruption crime prevention is a condition sine qua non in corruption crime eradication. Based on the condition of characteristic and/or functions of state administration judiciary which is not merely repressive (merely functioning as “judiciary”), this writing attempts to provide basic of understanding to the judicial development of state administration along with its preventive roles and functions which are related to law enforcement in corruption crime eradication in forms of or types of state financial lost as it is legally defined in law ratio of norm of Article 21 in Act of government administration.